Postharvest Quality of Fresh-Cut Carrots Packaged in Plastic Films Containing Silver Nanoparticles - Becaro, Aline A.; Puti, Fernanda C.; Panosso, Alan R. [UNESP]; Gern, Juliana C.; Brandão, Humberto M.; Correa, Daniel S.; Ferreira, Marcos D. (Springer Nature, 2016)
Active food packaging containing antimicrobial additive goes beyond traditional functions of packaging, once it can extend food shelf life maintaining its quality, safety and reducing postharvest losses by controlling food spoilage. Among several antimicrobial additives employed in polymeric films for packaging, metallic nanoparticles outstand due to its facility for synthesis, low-cost of production, and intense antimicrobial properties. In this work, extruded plain films of low-density polyethylene (LDPE) containing silver nanoparticles (AgNPs) embedded in SiO2 and TiO2 carriers (namely MS and MT, respectively) were produced and used as active packaging for maintaining the physicochemical and microbiological quality of carrots (Daucus Carota L. cv. Brasília). The neat (LDPE) and composite films containing MS and MT were characterized by scanning electron microscopy and permeability to oxygen and used for packaging fresh-cut sliced carrots stored at 10 °C for 10 days. After the storage time, the physicochemical properties of carrots were characterized, while the antimicrobial properties of films and AgNP migration were investigated. Our results revealed that both MT and MS packages showed antimicrobial activity even for films containing low concentration of AgNP. In addition, AgNP antimicrobial activity demonstrated to be carrier-dependent, once MT-LDPE showed improved performance compared to MS-LDPE. Regarding the physicochemical properties of packaged carrot, lower soluble solids and weight loss and higher levels of ascorbic acid were observed for carrots packaged with MT-LDPE films (compared to MS-LDPE), leading to a better postharvest quality conservation. Such differences observed in physicochemical properties of carrots are related to the distinct antimicrobial and film permeability properties for each composite film. In addition, under the conditions employed in this study, AgNP migration from the packages to fresh-cut carrot was not observed, which is highly desirable for food packaging safety, indicating the potential of such active packages for food preservation application.
Keywords: Daucus carota L; Food packaging; Migration; Permeability; Postharvest quality